EFEKTIVITAS PENERAPAN MEDIA PEMBELAJARAN AUDIO-VISUAL POWTOON TERHADAP HASIL BELAJAR SISWA SMP MATERI KEGIATAN EKONOMI - Huziana Huziana; Aminuyati Aminuyati; F.Y. Khosmas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe purpose of this research was to know the effectiveness of the application of powtoon’s audio-visual learning media. This research was conducted using pre-experimental design with the one-group pretest-posttest design. The subject of this study was 7th-grade students of smp 8. The techniques of  Data collection were direct observation technique, direct communication technique, and measurement technique. The tools of Data collecting in this research were interviews and student worksheets result based on data analysis, the results of the normality test state that the results of residual values are normally distributed with a significant value of 0.675 = 0.05. While the results of the hypothesis test state that Ho is rejected and Ha is accepted based on the sig value. (2-tailed) at the value of the pretest and posttest with a value of 0,000 which means smaller than 0.05. It showed that there were significant differences after the application of the Powtoon’s audio-visual learning media. In conclusion, teaching and learning activities with the application of Powtoon's audio-visual learning media on the economic subject in the 7th grade 8 Pontianak class showed very effective criteria for the process of improving student learning outcomes with an effect size in the amount of 1.64. Keywords: Effectiveness, Powtoon’s Audio-Visual Learning Media